PENGARUH MEDIA PEMBELAJARAN MONALISA (MONOPOLI PANCASILA TERHADAP KARAKTER KEWARGANEGARAAN SISWA KELAS X TPM DI SMK NEGERI 1 DRIYOREJO - Sonya Riri Safitri; Siti Maizul Habibah Sitihabibah; Listyaningsih listyaningsih; Rianda Usmi Riandausmi (STKIP Subang, 2026)
This study was motivated by the low level of civic character among students in Pancasila Education lessons. One strategy to address this issue is the use of an innovative and engaging instructional tool known as